2016
DOI: 10.17323/1814-9545-2016-1-205-224
|View full text |Cite
|
Sign up to set email alerts
|

Always Online: Using Mobile Technology and Social Media at Home and at School by Modern Teenagers

Abstract: Abstract. Students of Moscow schools and other educational institutions between the ages of 16 and 18 years old were surveyed to assess how Russian schools use modern methods of e-learning, mobile technologies, and social media in the learning process. The sample covered 3,194 respondents. The study describes three waves of Russian school informatization and the challenges the system has been facing over the last five years: the extensive use of mobile phones and PDAs with high-speed access to the Internet by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Social media has become a natural habitat for modern adolescents, who use mobile devices all the time [Koroleva 2016a]. When a school student creates a profile, they add friends, post content, join communities, etc.…”
Section: Interest Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media has become a natural habitat for modern adolescents, who use mobile devices all the time [Koroleva 2016a]. When a school student creates a profile, they add friends, post content, join communities, etc.…”
Section: Interest Research Methodsmentioning
confidence: 99%
“…Vkontakte (VK) seems to be largely prioritized among school students: 86% of the respondents reported having their primary social media accounts on this website [Koroleva 2016a]. The Vkontakte newsfeed is made up of the content posted by the user's friends and Vkontakte communities the communities that he/she follows.…”
Section: Interest Research Methodsmentioning
confidence: 99%
“…We believe that the investigation of adolescent online behavior can be a step in the right direction towards the development of such methods. Social media has become a natural habitat for modern adolescents, who use mobile devices all the time [Koroleva 2016a]. When a school student creates a profile, they add friends, post content, join communities, etc.…”
Section: Interest Research Methodsmentioning
confidence: 99%
“…Checking their inbox and scrolling through newsfeeds on social media regularly have become an everyday ritual for adolescents [Koroleva 2016b]. Vkontakte (VK) seems to be largely prioritized among school students: 86% of the respondents reported having their primary social media accounts on this website [Koroleva 2016a]. The Vkontakte newsfeed is made up of the content posted by the user's friends and…”
Section: Interest Research Methodsmentioning
confidence: 99%
“…In support of this view, a study investigated students' use of mobile devices (tablet PCs, Laptops and smartphones) and it found that students generally used smartphones in classes (Robert & Rees, 2014). Supporting educational innovations, technologies, developments and policies such as "Bring your Own Device" (BYOD) (Joyce-Gibbons et al, 2018;Koroleva, 2016) and on the other hand taking precautions against students' use of such devices can seem to be conflicting. This contradiction can also be seen in the literature.…”
Section: Smartphone Usage In Classmentioning
confidence: 99%